Behavioral changes in female Swiss mice exposed to tannery effluents - Sabrina Ferreira de Almeida (Revista Ambiente & Água, 2016)
Among the anthropic activities generating potentially toxic residues are those involved with bovine hide processing (tannery industries). However, knowledge is scant regarding the damage caused to the health of various organisms by tannery waste and studies are rare, especially in mammalian experimental models. This study therefore aimed to evaluate the physical and behavioral effects of the exposure of female Swiss mice to tannery effluent. To accomplish this, for a period of 15 days the animals were fed tannery effluent diluted with water in the following concentrations: 0% (control group, received only potable water), 5% and 10%. The body mass of the animals was evaluated at the beginning and end of the experiment, as well as the daily consumption of water and food. After 15 days of exposure to the effluent, the animals were submitted to the elevated plus maze (predictive of anxiety) and the forced swim test (predictive of depression). The treatments did not affect the animals' body mass, either in eating behavior or in consumption of water. However, it was found that the animals that ingested tannery effluent concentrations of 5% and 10% exhibited an anxiolytic (lower level of anxiety, greater percentage of time in the open arms, longer time and frequency in the diving behavior, less time of lurks and less frequency of freezing) and an antidepressant effect (more time in climbing behavior and less time of immobility) when compared to the control group. It was concluded that the exposure of female Swiss mice to tannery effluents (5% and 10% diluted with water) causes behavioral changes, possibly related to the neurotoxicity of this waste, without causing physical changes in the animals.